KARAKTERISTIK PENDERITA LEUKEMIA YANG DIRAWAT INAP DI RSUP H. ADAM MALIK TAHUN 2014-2016 - Meilita V Sinaga; Fazidah A Siregar; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Leukemia is a disease problem especially for children. In Indonesia (2006) the proportion of leukemia was ranked 5th (5.93%) of all cancer patients admitted to the hospital. The purpose of this study was to determine the characteristics of Leukemia patients treated in RSUP. H. Adam Malik Medan in 2014-2016. This is descriptive study with case series design. Population is all data of leukemia patient that is 176 patient data. The sample of this study is the total population. Data was analyzed by Chi-Square and Mann Whitney Test. The result shows that largest proportion of respondens with leukemia was by age 5-14 years old (25.6%), males (56.8%), Islamic (72.2%), High School / Equal (39.2%), students (31, 8%),  outside Medan (83%), pale complaints (70.5%), specific symptoms of anemia (88.1%), LLA type of leukemia (38.1%), medical management with supportive therapy (43,8%), average length of stay 9.77 days, go home treatment (73.39%). There are differences age of leukemia patients by leukemia type and medical management of leukemia patients by leukemia type. There was no difference sex of leukemia patients by leukemia type, average length of stay by leukemia type, and leukemia type by circumstances when returning home.               It was suggested that patients who seek treatment with complaints leukemia immediately and should checked to the doctor so that if proven leukemia can be done early treatment then take medication regularly.  Keywords: Leukemia, Characteristics of Patients